Operative Fixation of Displaced Middle Third Clavicle (Edinburg Type 2) Fracture with Superior Reconstruction Plate Osteosynthesis - Dhoju, D; Shrestha, D; Parajuli, N P; Shrestha, R; Sharma, V (Kathmandu University Medical Journal, 2012)
Background Conservative management of middle third clavicle fracture has been recently reported with suboptimal outcomes. Despite higher nonunion rates in initial open reduction and internal fixation, understanding the problem better and taking in accounts of previous shortcomings, such fractures can be optimally treated by open reduction and internal fixation with reconstruction plate. Objective To study the outcome of middle third clavicle fracture treated with superior reconstruction plating in terms of function using Constant shoulder score, union time and rate, complications and patient satisfaction. Methods Twenty patients with displaced middle third clavicle fracture (Edinburg type 2) treated with open reduction and internal fixation with reconstruction plate implanted in superior surface were prospectively followed for at least one year after surgery. Results There were 20 patients, 16 males and 4 females. The mean age of the patients was 31.5 years with SD 11.5 years (range 15-60 years) and 5 patients (25%) had associated injuries. All fractures united in 16 weeks or less in near anatomic position with complication in 2 (5%) patients, one deep infection and one frozen shoulder which on subsequent management recovered well. There was no nonunion or implant failure. The average Constant score was 97.45 in one year follow up and the patients were relatively satisfied with the treatment.The most common indication (25%) for hardware removal was young age of the patient, hardware prominence and occasional discomfort Conclusion This small series shows that displaced midshaft clavicle fracture can be optimally treated with operative fixation implanting the reonstruction plate in superior surface with six cortical purchases on either side and supervised physiotherapy, although subsequent surgery for implant removal might be necessary. DOI: http://dx.doi.org/10.3126/kumj.v9i4.6346 Kathmandu Univ Med J 2011;9(4):286-90